Development of A Technology-Based Storybook Model for Moral Intelligence in Early Childhood - Puspita, Yenda; Raharjo, Semiono; Fauziddin, Mohammad; Azhar (Proceedings of International Conference on Islamic Civilization and Humanities, 2023)
This research is motivated by the low interest in reading in children today. Children prefer watching TV and playing with gadgets because they display more moving images to attract attention. This study aims to produce a digital-based storybook product to improve the moral intelligence of early childhood that is valid, effective, and practical. This research is a research and development methodology following the development of the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The subjects of this study consisted of validators, namely two material experts and one media expert, and testing the practicality of product use on 8 ECE teachers. The product trial was conducted on 20 group B children at Ar Rehan Kindergarten. Data were collected through observation, interviews, and documentation, as well as using a questionnaire. The research results were obtained from validating two material experts by 93%, media expert validation by 87%, eight teacher respondents by 93%, and the child’s response by 88%. The product trial obtained a value of 0.004 <0.05, which shows that digital-based storybooks can significantly and effectively increase children’s moral intelligence in Ar Rehan Kindergarten.